Vergence and Strabismus in Neurodegenerative Disorders - Kang, Sarah L.; Shaikh, Aasef G.; Ghasia, Fatema F. (Frontiers in Neurology, 2018)
Maintaining precise eye alignment is necessary to generate a cohesive visual image. This involves the coordination of complex neural networks, which can become impaired by various neurodegenerative diseases. When the vergence system is affected, this can result in strabismus and disorienting diplopia. While previous studies have detailed the effect of neurodegenerative disorders on other eye movements such as saccades, relatively little is known about strabismus. Here we focus on the prevalence, clinical characteristics, and treatment of strabismus and disorders of vergence in Parkinson’s disease, spinocerebellar ataxia, Huntington disease, and multiple system atrophy. We find that vergence abnormalities may be more common in these disorders than previously thought. In Parkinson’s disease, the evidence suggests that strabismus is related to convergence insufficiency; however it is responsive to dopamine replacement therapy and can therefore fluctuate with medication “on” and “off” periods throughout the day. Diplopia is also established as a side effect of deep brain stimulation and is thought to be related to stimulation of the subthalamic nucleus and extra-ocular motor nucleus among other structures. In regards to the spinocerebellar ataxias, ocular motor symptoms are common in many subtypes, but diplopia is most common in type 3 spinocerebellar ataxia also known as Machado-Joseph disease. Ophthalmoplegia and vergence insufficiency have both been implicated in strabismus in these patients, but cannot fully explain the properties of the strabismus, suggesting the involvement of other structures as well. Strabismus has not been reported as a common finding in Huntington disease or atypical parkinsonian syndromes and more studies are needed to determine how these disorders affect binocular alignment.